Radical cystectomy in patients over 80 years old in Quebec: A population‐based study of outcomes. Issue 7 (8th February 2015) - Zakaria, Ahmed S.; Santos, Fabiano; Tanguay, Simon; Kassouf, Wassim; Aprikian, Armen G.
<x xml:space="preserve">Abstract</x> Objectives To document radical cystectomy (RC) outcomes in patients over 80 years old across Quebec during the years 2000–2009 and to examine potentially related factors. Methods Within Quebec health insurance medical services database, we identified patients over 80 years who underwent RC. The outcomes analyzed were post‐operative complications, mortality rates at 30, 60 and 90 days and overall survival. Results A total of 275 patients over 80 years old had RC performed in 38 hospitals across Quebec. Among them, 33% had major post‐operative complications with 16% having more than one complication. Mortality rates at 30, 60 and 90 days were 5.8%, 9.8% and 13% respectively. 44.3% of RCs were performed in seven academic hospitals with mortality rates of 2.5%, 6.5% and 9% respectively. Community hospitals had mortality of 8.5%, 12.4% and 16.3% respectively (P < 0.001). The cohort 5‐year overall survival rate was 27%. The presence of post‐operative complications and the number of complications negatively affected overall survival (P < 0.001) Conclusion Patients over 80 years of age have high post‐RC mortality rates, especially at 90 days. In addition, it appears that they have lower post‐operative mortality if their RCs were performed in academic centers. Mortality rates and complications can be used when obtaining informed consent. J. Surg. Oncol. 2015 111:917–922. © 2014 Wiley Periodicals, Inc.